Revolution and democracy in Ghana - Haynes, Jeffrey, 1953- author.
1 online resource (222 pages).
Keywords: "This book analyses Flight-Lieutenant Jerry Rawlings' plans for radical democratisation in Ghana, involving ordinary people directly in the country's political and economic decision-making processes. Rawlings came to power in Ghana in late 1981 determined to restructure the characteristics of Ghana's political and economic systems. Despite Rawlings' aim to bring ordinary Ghanaians into the decision-making process, his regime was still heavily dependent on the support of the military and attempts at direct democracy ultimately ended in failure. Outside analysts have viewed his plans as one of Africa's most draconian economic reform programmes. The book traces this turbulent period of Ghana's history, showing Rawlings' development from a fiery revolutionary to a democracy-supporting politician adept at winning elections. It investigates how, despite frequent coup attempts and the loss of most of its original civilian support base, the regime was able to remain in power, overseeing a halt to economic decline and a return to growth. Building on over thirty years of research, including contemporaneous interviews conducted by the author during Ghana's 'revolutionary' period, this book will be of interest to researchers of African history and politics"--